Activation of the NMDA receptor–neuronal nitric oxide synthase pathway within the ventral bed nucleus of the stria terminalis mediates the negative affective component of pain. (15th May 2017) - Deyama, Satoshi; Sugano, Yaya; Mori, Sakura; Amano, Taiju; Yoshioka, Mitsuhiro; Kaneda, Katsuyuki; Minami, Masabumi
Abstract: Pain consists of sensory and affective components. Although the neuronal mechanisms underlying the sensory component of pain have been studied extensively, those underlying its affective component are only beginning to be elucidated. Previously, we showed the pivotal role of the ventral part of the bed nucleus of the stria terminalis (vBNST) in the negative affective component of pain. Here, we examined the role of glutamate-nitric oxide (NO) signaling in the affective component of pain in rats using a conditioned place aversion (CPA) test. Intra-vBNST injection of either CNQX (an AMPA receptor antagonist) or MK-801 (an NMDA receptor antagonist) dose-dependently attenuated intraplantar formalin-induced CPA (F-CPA) without reducing nociceptive behaviors. In vivo microdialysis showed that extracellular oxidative NO metabolites (NOx) levels were significantly increased by intraplantar formalin injection. Intra-vBNST injection of NPLA (a selective neuronal NO synthase (nNOS) inhibitor), c-PTIO (a NO scavenger), or ZL006 (a postsynaptic density-95 (PSD-95)-nNOS interaction inhibitor) dose-dependently suppressed F-CPA without attenuating nociceptive behaviors. Intra-vBNST injection of NOR3 (a NO donor) produced CPA in a dose-dependent manner in the absence of noxious stimulation. Furthermore, whole-cell patch-clamp electrophysiology in the vBNST slices revealed that NOR3 induced depolarization of hyperpolarization-activated cation current ( I h )-positive vBNST neurons, which was blocked by the NO scavenger. These results suggest that activation of glutamatergic transmission and subsequent nNOS-derived NO production within the vBNST mediate the negative affective component of pain and that NO-evoked excitation of I h -positive vBNST neurons may be among the cellular mechanisms underlying pain-induced aversion. Highlights: Blockade of glutamatergic transmission in the vBNST reduces pain-induced aversion. Painful stimulus increases NO metabolites in the vBNST. Blockade of nNOS-derived NO in the vBNST reduces pain-induced aversion. Intra-vBNST injection of NO donor produces aversion. NO-evoked excitation of vBNST neurons may be critical for pain-induced aversion.